Peculiarities of investigated characteristics of Lithuanian pistol and rifle shooters training and sport performance - Gulbinskiene, V.; Skarbalius, A. (Ugdymas. Kuno Kultura. Sportas, 2009)
The purpose was to identify the peculiarities of selected training and sport performance characteristics: 1. training strategies, 2. the body sway and 3. mental fitness. Methods: we analysed the sport performance and training characteristics and applied interviews with elite and Lithuanian shooters. The body sway was studied applying the method of static posturography. The subjects were standing in four postures. Mental fitness of the shooters was evaluated 30 min before the start using CSAI-2 methodology and adapted SCAT methodology. The shooters were divided into two groups according to their sports performance: the high and the moderate mastery groups. Statistical analyses was made applying the SPSS 11.0 statistical package Results: 1. The Lithuanian women pistol shooters` mean age of the fi rst three place winners corresponded to that of the elite athletes, however the sports results (p < 0.001) were signifi cantly lower. We indicated the following reasons: they trained less than the elite shooters, their specifi c training was inappropriate (p < 0.001), their mental fitness and competition experience were inappropriate (p < 0.001). 2. The trajectory of the COP in a specifi c posture (legs at shoulder length, arms down; posture without the pistol; posture with the pistol) was signifi cantly (p < 0.05) different (Fig. 1, Masalskyte et al., 2002) between high and moderate mastery shooters but not in general posture (folded legs and arms down). The results suggested developing shooters` posture from the very beginning of training. 3. The Lithuanian shooters` level of anxiety before the starts showed the importance of the duration of exercise and competition experience because the difference between their indices and those of elite shooters was signifi cantly less (p < 0.001). Conclusions: On the basis of sport performance as a multidimensional construct which requires to select the main factors of athlete trainability we conclude that Lithuanian pistol and rifle shooters need a training programme that improves posture stability; they should increase their international competitive experience and have to monitor sport fi tness in order to manage psychological stress, and model a further training programme. Social conditions might be the main problem of the Lithuanian shooters to terminate their sport career too early.